Estudio de factibilidad técnico y económica para la creación de una planta envasadora de agua mineral en bidones en la parroquia de Manuel Cornejo Astorga ubicada al sur del cantón Mejía - Granda Cango, Edwin Alexis (2022)
Was considered the market meta to province of Santo Domingo de los Tsáchilas as in the which there are many sectors where the inhabitants ingest poor quality water from rivers and springs with microorganisms that are harmful to their health; therefore, the objective of this project is to carry out a feasibility study for the creation of packaging plant of water bottle plant to sirve this province, the type of research is descriptive and the research method is inductive and analytical synthetic, for the collection of the information, the bibliographic methods and documentary analysis were used, with this the market study was carried out analyzing the offer and the demand that allowed calculating the unsatisfied demand, then the technical, economic and financial study was carried out. The results were, an unsatisfied demand of 283,016,171.96 liters of water per year, the embazadora plant will be located in the Parish of Manuel Cornejo Astorga located south of the Mejía canton in the Zarapullo Bajo neighborhood with the name of "AGUA NATURAL EA SA”, the size or capacity will be 38016 liters of water per day collected from a spring which will be purified for packaging in 20 liter drums, with the economic analysis the total investment of $67645.04 dollars was established and finally, when carrying out the financial study of the project, the feasibility for the creation of the plant was determined with a Net Present Value of $16423,8 dollars and an Internal Rate of Return of 18%, considering our project as feasible for its execution.